Solution structure of the phosphoryl transfer complex between the signal transducing proteins HPr and IIA(Glucose) of the Escherichia coli phosphoenolpyruvate:sugar phosphotransferase system - Wang, Guangshun (Oxford University Press, 2000)
The solution structure of the second protein–protein complex of the Escherichia coli phosphoenolpyruvate: sugar phosphotransferase system, that between histidine-containing phosphocarrier protein (HPr) and glucose-specific enzyme IIA(Glucose) (IIA(Glc)), has been determined by NMR spectroscopy, including the use of dipolar couplings to provide long-range orientational information and newly developed rigid body minimization and constrained/restrained simulated annealing methods. A protruding convex surface on HPr interacts with a complementary concave depression on IIA(Glc). Both binding surfaces comprise a central hydrophobic core region surrounded by a ring of polar and charged residues, positive for HPr and negative for IIA(Glc). Formation of the unphosphorylated complex, as well as the phosphorylated transition state, involves little or no change in the protein backbones, but there are conformational rearrangements of the interfacial side chains. Both HPr and IIA(Glc) recognize a variety of structurally diverse proteins. Comparisons with the structures of the enzyme I–HPr and IIA(Glc)–glycerol kinase complexes reveal how similar binding surfaces can be formed with underlying backbone scaffolds that are structurally dissimilar and highlight the role of redundancy and side chain conformational plasticity.